The Differences Between Childhood and Adult Onset Antiphospholipid Syndrome - Wincup, Chris; Ioannou, Yiannis (Frontiers in Pediatrics, 2018)
Antiphospholipid syndrome (APS) is a rare autoimmune disease of unknown etiology that represents a leading cause of acquired thromboembolism and recurrent miscarriage. It is characterized by the persistent elevated presence of pathogenic antiphospholipid auto-antibodies directed against cardiolipin, ß2-glycoprotein-I and / or a positive lupus anticoagulant test. As with many autoimmune disorders, the pathogenesis of APS is believed to be the result of a complex interaction between environmental triggers and genetic predisposition. Although more common in adults, APS occasionally manifests in the neonatal period and throughout childhood. Adut-onset APS classification criteria are poorly validated to the pediatric population (in which pregnancy related complications are seldom seen) and as a result, assessment of the prevalence of the disease in childhood is difficult. Thromboembolic events seen in children include deep venous thrombosis in addition to stroke and pulmonary embolism, which can lead to significant long-term disability. The disease can be classified as either primary (when occurring in isolation) or secondary, in which the disease is diagnosed in the context of another underlying disease, most commonly systemic lupus erythematosus. A variety of laboratory and clinical difference are seen between pediatric and adult-onset APS. The marked female predominance seen in adult-onset disease is less evident in childhood where the gender split is more evenly spread. In addition, children with APS are at a higher risk of recurrent thromboembolism than adults. The treatment of childhood-onset APS is challenging due to a lack of large-scale prospective studies in the pediatric population. Therapeutic options are often based upon treatment guidelines that have been based upon literature from the adult-onset form of the disease. In the majority of cases, treatment is focused on the prevention of further thrombosis through treatment with long-term anti-coagulation therapy. The evidence for the use of antiplatelet agents (such as aspirin) and hydroxychloroquine is inconclusive. It is important to remember that anti-coagulation can have significant lifestyle implications for the child with APS and it is essential to consider potential implications relating to school and recreational activities, with contact sports often discouraged due to the increased risk of bleeding.